HUBUNGAN ANTARA MOTIVASI DAN KEMANDIRIAN BELAJAR DENGAN PRESTASI BELAJAR MAHASISWA MATA KULIAH PELAYANAN KELUARGA BERENCANA (PRODI DIII KEBIDANAN POLITEKNIK TEGAL) - Susiana Sariyati kebidanan (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2012)
Susiana Sariyati NIM : S541002033,2011. Relationship Between Motivation And Self Learning By Teaching Student Learning Achievement Family Planning Services Diploma Midwifery Politeknik Tegal. Supervising commission I : Dr.Nunuk suryani, M.pd. Advisors II : Dr.Hermanu J, M.pd.thesis : postgraduate program of sebelas maret university Surakarta. This research aims to identify the relationship between motivation and academic achievement of student in the third semester course in family planning services study program DIII midwifery politeknik tegal, to know the relationship between self study and academic achievement of students in the third semester course in family planning services diploma midwifery politeknik tegal, know the relationship between motivation and self study the learning achievement of student in the third semester course in family palnning services study program DIII Midwifery politeknik tegal.The research was conducted to the student in study program DIII midwifery politeknik tegal in the third semester student in 2011/2012. this research uses cross sectional approach. variabels examined only one time measurment measured only within a certain time. population in this research are 130 respondents. the sampling technique is simple random sampling with asample of 98 respondents. test the validity of the instrument using the product moment correlation coefficient and the reliability test using cronbach alpha. analysis technique using a simple correlation, multiple correlation and multiple regression with significance level of 5%.The result there is a relationship between motivation and academic achievement subject family planning services of 0,559, the relationship between self study courses and academic achievement family planning services of 0.431, while the results of multiple regression analysis found that jointly between motivation and self study related with learning achievement in the course family planning services of 0.650.It can be concluded that there is: 1) positive and significant relationship between motivation and academic achievement family planning services subject. 2) there are positive and significant relationship between self study courses and academic achievement family planning services. 3) thre is a relationship between motivation and self study the learning achievement of students subject family planning services study program DIII Midwifery politeknik tegal. Keywords : Motivation, Self Learning, Learning Achievement.